Analisis Pemanfaatan Dana Desa Dalam Pemberdayaan Masyarakat di Desa Baji Mangngai Kecamatan Mandai Kabupaten Maros - Rahmayanti (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
The community empowerment programs implemented in Baji Mangngai Village include increasing food crop production through the provision of fertilizers and agricultural processing support, enhancing livestock production through the distribution of livestock breeding stock along with livestock housing facilities, and providing appropriate technology training for agricultural and livestock activities. However, several factors influence the utilization of village funds for community empowerment in Baji Mangngai Village. Supporting factors include government support through proactive policies, training programs, adequate infrastructure, and active community participation. Meanwhile, the inhibiting factors consist of delays in village fund disbursement, limited community involvement in the Village Development Planning Meetings (Musrenbang), fluctuations in fertilizer supply and livestock quality, as well as inadequate initial knowledge, monitoring, and evaluation of program activities. Overall, the utilization of village funds for community empowerment in Baji Mangngai Village has made a positive contribution to village development and the improvement of community welfare. Through continuous evaluation and improvements in program management and implementation, Baji Mangngai Village can continue progressing toward sustainable and inclusive community empowerment.